2007
DOI: 10.1017/s1049023x00005197
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for Burn Disasters: Predictors of Improved Perceptions of Competency after Mass Burn Care Training

Abstract: Introduction:Prehospital and community hospital healthcare providers in the United States must be prepared to respond to burn disasters. Continuing education is the most frequently utilized method of updating knowledge, skills, and competence among healthcare professionals. Since preparedness training must meet multiple educational demands, it is vital to understand how participants'work and educational experience and the program's content and delivery methods impact knowledge acquisition, and how learning inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…Results of recently published studies, suggested that a continuing education training course of pre-hospital and community hospital healthcare providers could be effective in improving the participants' knowledge and their abilities and confidence toward burn disaster management. More importantly, the changes in knowledge, abilities, and confidence appear to be translated to an enhanced sense of competence to perform during a burn disaster [7,27]. Facing a burn disaster, any given facility can handle a limited workload at one time [28].…”
Section: Preparedness and Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of recently published studies, suggested that a continuing education training course of pre-hospital and community hospital healthcare providers could be effective in improving the participants' knowledge and their abilities and confidence toward burn disaster management. More importantly, the changes in knowledge, abilities, and confidence appear to be translated to an enhanced sense of competence to perform during a burn disaster [7,27]. Facing a burn disaster, any given facility can handle a limited workload at one time [28].…”
Section: Preparedness and Planningmentioning
confidence: 99%
“…Instead, in a major burn accident, a field triage protocol for rapid evaluation of burn injuries may be all what is needed. Detailed assessment of injuries of burn casualties is practical only in a specialized clinical setting [27]. It must be acknowledged though that every rapid triage protocol has inherent significant limitations [44,45].…”
Section: Triagementioning
confidence: 99%
“…However, several states reported finding it difficult to convey a coherent message of managing multiple burn-injured patients, when the general audience felt uncomfortable managing even the first burn-injured patient. 1,[26][27][28][29][30][31] (The BTHPP is now located in the U.S. DHHS Office of the Assistant Secretary for Preparedness and Response [ASPR] and referred to as the Hospital Preparedness Program [HPP].) 32 The first year this program included offering a wide-reaching series of presentations regarding the aims for the burn surge disaster program and focused on historical burn disasters that wreaked havoc for first responders, first receivers, trauma, and burn centers alike.…”
Section: Introductionmentioning
confidence: 99%
“…Critical partners include EMS agencies as well as hospitals with and without burn centers. 30,31,33,34 To meet the educational need, those involved with the burn surge disaster program evaluated national standardized educational programs. Key criteria for selection included; current science validated by a national stakeholder organization for the care of a burn-injured patient, 35 a core component involving the management of a surge of burn-injured patients, and was approved to offer the relevant educational credits recognized by the various professional organizations to include physicians, nurses, and paramedical personnel.…”
Section: Introductionmentioning
confidence: 99%
“…Frequent education training courses for such staff have to be carried out [9]. Experience and preparedness are preconditions for alleviating disaster events [10].…”
Section: Introductionmentioning
confidence: 99%